2017 Annual Report Digest of the Renal Epidemiology Information Network (REIN) registry. (4th July 2019) - Lassalle, Mathilde; Monnet, Elisabeth; Ayav, Carole; Hogan, Julien; Moranne, Olivier; Couchoud, Cécile; ,
Summary: The French Renal Epidemiology and Information Network (REIN) registry started in 2002 with the goal to provide a tool to evaluate renal replacement therapy (RRT) practices and outcomes, to provide data for research and to support public health decisions related to end‐stage renal disease ESRD. This summary presents the incidence and prevalence of RRT including kidney transplantation and wait‐listing activity in 2017, and patients' survival and trends over 5 years. In 2017, 11 543 patients started RRT for ESRD, that is, incidence of 172 pmp. Between 2012 and 2017, the incidence of RRT increased by 1% per year [CI 95% (0.0; +2.0)]. On 31 December 2017, 87 275 patients were receiving RRT, that is, prevalence of 1294 pmp, 55% on dialysis, 45% with a functioning transplant. In 2017, 3782 kidney transplantations have been performed including 16% from a living donor, 13% being retransplantations and 15% pre‐emptive transplantations. The median time on the waiting list was 19.7 months when only taking into account active waiting periods on the list. In 2017, 5280 new patients were registered on the renal transplant waiting list (i.e. 78.7 pmp). The number of patients considered as 'inactive' represented 45% of the patients on the list.